(untitled) (Web of Teachers: Inderscience Research, 2025)
The article presents an overview of studies devoted to dry milk whey, a valuable by-product of the dairy industry. The methods of dry milk whey production, its composition and properties, as well as the potential for use in various industries, including the food industry, agriculture and biotechnology are considered. Particular attention is paid to the prospects for the use of dry lactic acid as a functional ingredient for food enrichment, a feed additive for animals and a substrate for the production of valuable bioproducts.